2022
DOI: 10.3389/fnhum.2022.838692
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Alzheimer’s Disease: From Pathology to Imaging

Abstract: Alzheimer’s disease (AD) is a debilitating brain disorder that afflicts millions worldwide with no effective treatment. Currently, AD progression has primarily been characterized by abnormal accumulations of β-amyloid within plaques and phosphorylated tau within neurofibrillary tangles, giving rise to neurodegeneration due to synaptic and neuronal loss. While β-amyloid and tau deposition are required for clinical diagnosis of AD, presence of such abnormalities does not tell the complete story, and the actual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 240 publications
0
18
0
Order By: Relevance
“…Additionally, clinical neuroimaging studies have demonstrated the association between iron accumulation and myelination in normal aging [ 140 , 141 ] as well as the association between tau accumulation and iron in AD patients [ 142 ]. Cerebrospinal fluid levels of iron transport proteins are also associated with cognitive decline in AD [ 137 ].…”
Section: Exploring Other Targets Implicated In Both Myelin Repair and Admentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, clinical neuroimaging studies have demonstrated the association between iron accumulation and myelination in normal aging [ 140 , 141 ] as well as the association between tau accumulation and iron in AD patients [ 142 ]. Cerebrospinal fluid levels of iron transport proteins are also associated with cognitive decline in AD [ 137 ].…”
Section: Exploring Other Targets Implicated In Both Myelin Repair and Admentioning
confidence: 99%
“…Inflammatory milieu such as the presence of activated microglia and associated cytokine production may also play a role in inducing ferritin toxicity to OLs [ 144 ]. Additionally, excess iron in animal models can increase APP, inhibit α-secretase cleavage, and increase β-secretase cleavage [ 137 ]; however, APP, in turn, can stabilize the iron export protein ferroportin (Fpn) [ 137 , 148 ], which is involved in OL maturation and myelination [ 149 ]. Another iron import protein, Divalent metal transporter 1, is involved in APP processing and co-localizes with Aβ plaques [ 150 ], and its deletion is associated with reductions in OPC maturation and myelination [ 147 ].…”
Section: Exploring Other Targets Implicated In Both Myelin Repair and Admentioning
confidence: 99%
See 1 more Smart Citation
“…A plaques have been considered for many years as the main cause of neurotoxicity in AD onset and progression, but development of A plaques is a common phenomenon in most people during aging and does not necessarily lead to cognitive decline. As a matter of fact, based on postmortem analyses, individuals with A plaques and large Fe deposits are highly likely to develop dementia [ 56 ], possibly implicating that a tendency towards brain Fe accumulation could be a factor increasing AD susceptibility. In addition, during the onset of AD, microglial cells are believed to protect the brain by incorporating extracellular A filaments that are prone to bind several metals, such as Cu, Zn and Fe [ 49 , 57 ], until their maximum buffering capacity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a neurodegenerative disease with insidious onset, characterized by progressive cognitive dysfunction and memory impairment ( Morató et al, 2022 ). The main pathological features of AD are decreased a number of cortical neurons, nerve fiber tangles, and senile plaque deposition ( Counil and Krantic, 2020 ; Tran et al, 2022 ). With the increase of age, the incidence of AD increases gradually, which seriously affects the quality of life and brings a great burden to families.…”
Section: Introductionmentioning
confidence: 99%